eHalalCosmetics4u: combining faith and beauty in crafting the perfect makeup for Muslim women - Ahmad Dahlan, Abdul Rahman; Hassany, Sakina; Etae, Sitifatimoh; Kalong, Suwabah (IJSRP INC., 2017)
This paper proposes a customer to customer or C2C service platform, named eHalalCosmetics4u. This trusted conceptual platform serves Muslims to sell and buy variety of quality and Halal cosmetic products at affordable price through online as well as through network of mosques. This platform has the ability to provide convenience, secured and friendly interfaces to advertise, sell and buy halal cosmetics products. Literature reviews, nine (9) blocks of Business Model Canvas (BMC) and Value Proposition Design Canvas (VPC) framework and interviews are used as methodology for this paper.